Pure Squamous Cell Carcinoma of Renal Pelvis: A Rare Case Report (Purbanchal University Health Journal, 2024)
Pure squamous cell carcinoma of renal pelvis is a rare malignancy usually associated with nephrolithiasis. There is difficulty in early diagnosis of such rare neoplasm because of non-specific clinical and radiological features. We report a case of squamous cell carcinoma of left renal pelvis in a 60 year old male with history of long standing renal calculi. After detailed workup, he underwent radical nephrectomy and the histopathological examination revealed squamous cell carcinoma of renal pelvis.